Recently evolved diversity and convergent radiations of rainforest mahoganies (Meliaceae) shed new light on the origins of rainforest hyperdiversity. Issue 2 (5th June 2015) - Koenen, Erik J. M.; Clarkson, James J.; Pennington, Terence D.; Chatrou, Lars W.
Summary: Tropical rainforest hyperdiversity is often suggested to have evolved over a long time‐span (the 'museum' model), but there is also evidence for recent rainforest radiations. The mahoganies (Meliaceae) are a prominent plant group in lowland tropical rainforests world‐wide but also occur in all other tropical ecosystems. We investigated whether rainforest diversity in Meliaceae has accumulated over a long time or has more recently evolved. We inferred the largest time‐calibrated phylogeny for the family to date, reconstructed ancestral states for habitat and deciduousness, estimated diversification rates and modeled potential shifts in macro‐evolutionary processes using a recently developed Bayesian method. The ancestral Meliaceae is reconstructed as a deciduous species that inhabited seasonal habitats. Rainforest clades have diversified from the Late Oligocene or Early Miocene onwards. Two contemporaneous Amazonian clades have converged on similar ecologies and high speciation rates. Most species‐level diversity of Meliaceae in rainforest is recent. Other studies have found steady accumulation of lineages, but the large majority of plant species diversity in rainforests is recent, suggesting (episodic) species turnover. Rainforest hyperdiversity may best be explained by recent radiations from a large stock of higher level taxa.